Taking an ethics of care perspective on two university teacher training programmes - Bennoun, S.; Haeberli, P.; Schaub, M. (South African Journal of Higher Education, 2018)
This paper shows the usefulness and interest of taking an ethics of care perspective to evaluate university teacher training programmes. More precisely, in this case study we use the five elements of care identified by Tronto – attentiveness, responsibility, competence, responsiveness and trust – to assess two multiple-day training programmes offered at the University of Geneva. We show how small changes in our practice such as giving some choice to the participants over the topics addressed, adapting the schedule to meet the participants’ constraints or dedicating time slots specifically for the questions and concerns raised by the participants can have a big impact on the level of care provided. We moreover argue that this framework brings interesting and novel elements that appropriately “counterbalances” traditional evaluations that are usually implicitly based on notions such as performance, efficiency and measurability. Finally, we briefly explain how the ethics of care could be used a basis to not only evaluate but to rethink and elaborate training programmes.